Work Motivation and Self-Efficacy: Building Subjective Well-Being Teacher Raudhatul Athfal - Sri Lestari, Sugeng; Muarifah, Alif (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2022)
Purpose – Subjective well-being of a good teacher causes teachers to be more focused, productive, and confident that they can complete teaching tasks regardless of the difficulty. This study aims to determine the effect of self-efficacy and work motivation of teachers on sujective well-being.Design/methods/approach – This quantitative research was conducted by distributing questionnaires to 183 uncertified teachers. Obtained a sample of 118 teachers whose data were taken with area sampling. The measuring instrument used is the work motivation scale, self-efficacy scale, and subjective well-being scale. Research data is processed by multiple regression analysis with an assumption test.Findings – The results of the analysis test obtained R 0.644, 1 = 0.383 and 2 = 0.352 and a significance value of of 0.000 (ῥ < 0.001) providing an effective contribution of 41.85%. It shows that the hypothesis is accepted that there is a significant positive effect between the motivation and self-efficacy of teachers’ work on subjective well-being. The first minor hypothesis test has a partial coefficient value r of 0556 with a significance value of providing an effective contribution of 21.87%. There is a very significant positive influence between work motivation and subjective well-being. The results of the second minor hypothesis test have a partial coefficient value (r) of 0.571 with a significance value of 0.000 <0.01, giving an effective contribution of 19.57%. Some teachers did not have good subjective Well being in Raudhatul Athfal, Bantul Regency. There is a significant positive effect between teacher self-efficacy and subjective well-being. The higher the teacher’s self-efficacy, the greater the subjective Well being. The lower the self-efficacy, the lower the subjective well-being. Self-efficacy contributes 19.57%, and teacher work motivation contributes 21.87% to subjective well-being. Other factors influence the remaining 58.55%.Research implications/limitations – This study only explores internal factors and has not examined external factors that affect subjective well-being. This study’s limitations are that the three-dimensional items’ preparation does not suggest an unfavorable scale. Categorization of intrinsic motivation should be based on the type of teacher work motivation, not categorization based on high and low work motivation. Practical implications – Teachers can do their job well if they have high subjective well-being. It can be pursued by increasing work motivation and high self-efficacy both by the school and the teacher.Originality/value – This study is essential for teachers to have good work motivation and believe they can influence student learning outcomes, improving the teacher’s subjective well-being. Paper type Research paper